In vitro anti-neuroinflammatory and neuritogenic stimulatory effects of a medicinal mushroom lignosus rhinocerotis (Cooke) ryvarden / Syntyche Seow Ling Sing - Syntyche Seow , Ling Sing (2016)
Neuroinflammation and neurite degeneration are contributing factors leading to the progression of neuronal loss and age-related neurodegenerative diseases e.g Alzheimer’s and Parkinson’s disease. Current drug therapy for neurodegenerative diseases is ineffective with many side effects and it is palliative and manages only the symptoms of the diseases. In recent years, the attention of researchers has been inclined towards the alternative and complementary approaches, such as dietary supplementations and functional foods which have minimal side effects. Numerous neuroactive substances from natural sources as preventive and therapeutic agents for neurodegenerative diseases by promoting anti-neuroinflammatory and neuritogenic stimulatory potential have received extensive attention. Among the natural sources explored for anti-neuroinflammatory and neuritogenic stimulatory properties, medicinal mushrooms have shown huge potential. In the present study, four medicinal mushrooms were evaluated for cytotoxic, inhibition of nitric oxide (NO) production and neuritogenic stimulatory activities in murine BV2 microglial and rat pheochromocytoma (PC-12) cells. The preliminary results showed that the hot aqueous extract of Lignosus rhinocerotis sclerotium significantly (p < 0.05) inhibited NO production (75.57%) in lipopolysaccharides (LPS)-stimulated BV2 microglia and stimulated 20.99 ± 1.01% of neurite bearing cells in PC-12 cells that comparable to the positive control, 50 ng/ml of nerve growth factor (NGF). The hot aqueous extract of L. rhinocerotis sclerotium was not cytotoxic to BV2 and PC-12 cells after 48 hours of exposure. The hot aqueous extract of L. rhinocerotis sclerotium was further fractionated into three solvent fractions: ethyl acetate, n-butanol and aqueous fractions. The antineuroinflammatory and neuritogenic stimulatory effects of the solvent fractions and the underlying mechanisms were investigated. The results demonstrated that ethyl acetate and n-butanol fractions (125 and 250 μg/ml) inhibited the production of proinflammatory mediators and cytokines, including NO, prostaglandin E2 (PGE2), tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β), and the expressions of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), TNF-α, IL-1β and IL-6 in LPS-stimulated BV2 microglia. The anti-neuroinflammatory effects of ethyl acetate and n-butanol fractions are mediated through the suppression of the toll-like receptor 4 (TLR4), mitogen-activated protein kinases (MAPKs) (extracellular signal-regulated kinases1/2 (ERK1/2), stress-activated protein kinases/jun amino-terminal kinases (SAPK/JNK) and p-38 MAPK), protein kinase B (AKT) and nuclear factor-kappaB (NFκB) signaling pathways with the inhibition of the transcription factors, cyclic adenosine monophosphate (cAMP) response element-binding protein (CREB), activator protein 1 (AP-1) and NFκB. The ethyl acetate and n-butanol fractions (10 μg/ml) significantly (p < 0.05) stimulated a higher percentage of neurite bearing cells compared to NGF (50 ng/ml) without stimulating the production of NGF in PC-12 cells. The ethyl acetate and n-butanol fractions mimicked the neuritogenic activity of NGF by targeting the tropomyosin receptor kinase A (TrkA) receptor and activated the mitogen-activated protein kinase kinase (MEK)/ERK1/2 and phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling pathways with the phosphorylation of CREB, and leading to the increased expressions of neuritogenesis biomarker, the growth associated protein 43 (GAP43), tubulin alpha 4A (TUBA4A) and tubulin beta 1 (TUBB1) in PC-12 cells. In conclusion, the present findings demonstrated that L. rhinocerotis sclerotium mitigated neuroinflammation and stimulated neuritogenesis in BV2 and PC-12 cells, respectively.